If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4y + -7) + 9 = 0 Reorder the terms: -1(-7 + 4y) + 9 = 0 (-7 * -1 + 4y * -1) + 9 = 0 (7 + -4y) + 9 = 0 Reorder the terms: 7 + 9 + -4y = 0 Combine like terms: 7 + 9 = 16 16 + -4y = 0 Solving 16 + -4y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -4y = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -4y = 0 + -16 -4y = 0 + -16 Combine like terms: 0 + -16 = -16 -4y = -16 Divide each side by '-4'. y = 4 Simplifying y = 4
| -5(6n-6)+2n= | | 52=n | | N+11=25 | | 2.1x-2.3y+4.9x-0.7y= | | 11x^2-x-3=0 | | 3x^2-5x-3-8x+5-x^2= | | 4xy+2z-7xy-7z= | | -3-4z+2-z= | | 81=9z | | 3rs-6r+s-7rs+11r-s= | | 7y^2-9y+8-15y^2-9y+5= | | 7n^2+28n=0 | | 24a=312 | | x^2+6x-8=4+10x | | 7s+11=12+7s | | y=4+x | | 7a^5-9a^3+2a^4= | | 2xy+8yz-7xz-2xy= | | 14x+10y+16+12x-16y-10= | | -0.428(m+5)=3+2m | | 1.6x-3.3y-4.6x-6.8y= | | 5a^4-3a^3+2a^4= | | y=8-10 | | y=8-0 | | -5b^2+13b^2= | | (4x-2)*(4x-2)-40x-20+21=0 | | y=8+10 | | 8=m/7 | | y=8+0 | | ((4x-2)*(4x-2))-10(4x-2)+21=0 | | y=8+x | | x+x*0.07=30 |